2015
DOI: 10.1179/1607845415y.0000000001
|View full text |Cite|
|
Sign up to set email alerts
|

A mutational and expressional analysis of DNMT3A in acute myeloid leukemia cytogenetic subgroups

Abstract: In relation to DNMT3A expression, from the perspective of diagnostic application and its biological significance, it is difficult to accept its primacy over cytogenetic value in favorable and unfavorable subgroups and if so, we did not address this issue in our study due to sample size limitation. In intermediate subgroup, particularly in normal karyotype-AML, given the lack of convincing results, it seems unlikely that DNMT3A expression analysis could attract attention in diagnostic workup and risk prediction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Adult patients’ ( n = 128) in the range of 16–60 years, for whom diagnostic peripheral blood (PB) ( n = 76 with blast ≥30%) or bone marrow (BM) ( n = 52), samples were available and were included after obtaining Institutional Review Board approval and informing consent in accordance with the Declaration of Helsinki. Because of common treatment and to have a larger sample size, samples from previous studies were included . The patients were classified according to the French–American–British (FAB) Cooperative Group Criteria .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adult patients’ ( n = 128) in the range of 16–60 years, for whom diagnostic peripheral blood (PB) ( n = 76 with blast ≥30%) or bone marrow (BM) ( n = 52), samples were available and were included after obtaining Institutional Review Board approval and informing consent in accordance with the Declaration of Helsinki. Because of common treatment and to have a larger sample size, samples from previous studies were included . The patients were classified according to the French–American–British (FAB) Cooperative Group Criteria .…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA extraction and complementary DNA (cDNA) synthesis were performed as described previously . In this study, we established qRT‐PCR using primers dedicated to the sensitive detection of BECN1 mRNA (accession no.…”
Section: Methodsmentioning
confidence: 99%
“…These normal cytogenetic patients with isolated bi-allelic CEBPA (biCEBPA) or NPM1 mutation without FLT3-ITD are associated with a favorable prognosis, whereas FLT3-ITD or TP53 mutations are associated with a poor prognosis (3)(4)(5)(6). DNA methyltransferase 3A (DNMT3A) gene mutations are associated with hyperleukocytosis at disease presentation, the elderly, and a poor prognosis (7). Patients less than 60 years and with DNMT3A, FLT3-ITD, and NPM1 mutations had a shorter event-free survival (EFS) (P=0.047).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found that frequency of DNMT3A mutations in AML is 17%»30% and most of DNMT3A mutations are heterozygous 12,15,16,18 Besides Common DNMT3A R882 mutation, mutations of V897D, G543C and R478W are also found.…”
mentioning
confidence: 99%
“…20 Although there were many studies, there was no definite conclusion about effect of DNMT3A mutations on AML prognosis (Table 1). [15][16][17][18][19][20][21]26 FLT3 is the most frequently mutated gene in AML (Table 1), with an approximately 28%»34%of AML cases harboring FLT3 mutations 28,29 FLT3 have 2 kinds of mutations: an internal tandem duplication (ITD) in the juxtamembrane domain and a point mutation of the tyrosine kinase domain (TKD). Estimated 20-25% of AML cases harbor FLT3-ITD mutations, 27 and FLT3-ITDmutations in adult AML are associated with clinical features such as having higher white blood cell count and higher peripheral blood blast cell count.…”
mentioning
confidence: 99%